2020
DOI: 10.1002/tafs.10245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Underwater Video with Electrofishing and Dive Counts for Stream Fish Abundance Estimation

Abstract: Advances in video technology enable new strategies for stream fish research. We compared juvenile (age‐0) and adult (age‐1 and older) Brook Trout Salvelinus fontinalis abundance estimates from underwater video with those from backpack electrofishing and dive count methods across a series of stream pools in Shenandoah National Park, Virginia (n = 41). Video methods estimated greater mean abundance of adult trout than did one‐pass electrofishing, but video estimates of adult abundance were not different than est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Our estimates of detection using UACs were relatively high (0.521–0.634), likely due to the spatial scale of thermal refuges (<352.02 m 2 ) and the channel deflecting boulders limiting escapement from most refuges (e.g., Figure 2a). Previous studies indicate that turbidity or depth (Campbell et al, 2015; Ebner & Morgan, 2013) or sampling in more complex habitats (Hitt et al, 2021) can limit fish detection using UAC surveys. We found that detection was highest at lower brightness estimates, perhaps due to light backscattering during brighter conditions increasing glare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our estimates of detection using UACs were relatively high (0.521–0.634), likely due to the spatial scale of thermal refuges (<352.02 m 2 ) and the channel deflecting boulders limiting escapement from most refuges (e.g., Figure 2a). Previous studies indicate that turbidity or depth (Campbell et al, 2015; Ebner & Morgan, 2013) or sampling in more complex habitats (Hitt et al, 2021) can limit fish detection using UAC surveys. We found that detection was highest at lower brightness estimates, perhaps due to light backscattering during brighter conditions increasing glare.…”
Section: Discussionmentioning
confidence: 99%
“…We extracted counts of trout from each of the 161 video surveys similar to other studies in freshwater systems (Ebner & Morgan, 2013; Hitt et al, 2021). For each 15‐min video, one observer identified trout to the lowest taxonomic level possible using body coloration and morphometric characteristics (e.g., presence of adipose fin), and enumerated fish every 90 s, totaling 11 counts (i.e., surveys) per video.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Side-scan sonar technology provides opportunities to map underwater lake features such as substrate and coarse woody habitat (Koeller, 2014), and more recently, autonomous surface vessels have been developed to monitor invasive macrophyte growth through imagery and collection of depth information (Codd-Downey et al, 2021). Underwater videography has also shown continued utility to estimate fish richness and abundance (Ebner and Morgan, 2013;Wilson et al, 2014;Hitt et al, 2021), behavior (Coghlan et al, 2017) and habitat use Davis et al 1997(Pratt et al, 2005, largely because it is cost-effective and more widely tractable. Its use to conduct spatially-continuous assessments of littoral habitat, to our knowledge, has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%